Photocuring 3D printing anti-drying conductive gel material and preparation method thereof

By introducing polyethylene glycol and strong coordination bonds into the photocured 3D printed gel, an anti-drying and photocurable gel material is constructed, which solves the problem of easy drying and poor elasticity of existing gels at high temperatures, and achieves efficient anti-drying and good mechanical properties.

CN119505071APending Publication Date: 2025-02-25TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411710236.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing photocuring 3D printed gels are easy to dry at high temperatures and have poor elasticity, making it difficult to take into account good electrical conductivity and mechanical properties.

Method used

By introducing polyethylene glycol and strong coordination bonds into the covalent polymer network, a synergistic effect of non-covalent bonds and covalent bonds is used to construct a drying-resistant, photocurable 3D printed gel material. The gel uses acrylic acid as monomer and polyethylene glycol as solvent, and zirconium and zinc ions are added to provide strong coordination and conductivity.

Benefits of technology

The gel has excellent anti-drying performance, high elasticity and printability in high temperature environments, while maintaining good conductivity and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505071A_ABST
    Figure CN119505071A_ABST
Patent Text Reader

Abstract

The invention discloses a photocuring 3D printing anti-drying conductive gel material as well as a preparation method and application thereof, and belongs to the field of gel materials and 3D printing materials. The material is prepared from the following components in parts by mass: 40-60 parts of unsaturated polymer monomer; 40 to 60 parts of a solvent; 0.25 to 1 part of zirconium salt; 0 to 14 parts of zinc salt; 0.5 to 2 parts of a photoinitiator; and 0-0.03 part of a light absorber. The problems that existing photocuring 3D printing gel is easy to dry at high temperature and poor in elasticity are solved, and the gel material prepared through the method has good conductivity and mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a photocurable 3D printing anti-drying conductive gel material and a preparation method and application thereof, belonging to the field of gel materials and 3D printing materials. Background Art

[0002] Due to the low modulus, soft and deformable properties of soft materials, they have shown great application prospects in the fields of biomedicine, flexible sensing, soft robotics, etc. As a kind of soft material, hydrogel not only has a modulus close to that of human skin, high transparency, and dynamically adjustable adhesion, but also can be endowed with conductivity by introducing conductive ions, and can easily convert external stimuli into electrical signals, making them popular materials for use in the fields of tissue engineering, optical devices, biomedicine, actuators, etc.

[0003] Compared with traditional materials, hydrogels have shown their unique advantages in many aspects, such as controllable conductivity, high stretchability, excellent biocompatibility and reliable signal stability. However, there are still some challenges in hydrogel-based applications. Hydrogels usually have a short service life and are very easy to lose water at room temperature, which causes the gel structure to shrink, harden, deteriorate electrical stability and even lose conductivity. In order to solve this problem, organic solutions such as ethylene glycol, glycerol, ionic liquids, and low eutectic solvents began to be introduced into the gel system. Because they have a high boiling point, they are used to replace water as a solvent to prepare a more stable gel. However, the molecular weight of these solvents is small, so that the gel still has problems of solvent evaporation and leakage when used in a high temperature environment (above 35°C), which leads to rapid drying of the gel.

[0004] At present, there are many methods for gel molding, the most common methods are chemical casting and extrusion 3D printing. Although these molding methods can provide good stability for gel molding, they cannot prepare gels with complex structures, which greatly limits the application and development of gels in many fields. Among various 3D printing technologies, digital light processing (DLP) 3D printing technology and selective area transmission (LCD) 3D technology have attracted widespread attention due to their high printing rate and high printing resolution. They can quickly manufacture hydrogels with highly complex spatial geometries through ultraviolet light source projection technology. This high-precision and rapid molding method combined with gel materials provides a broader application prospect for gel materials.

[0005] Therefore, preparing ion conductive gels that can be photocured for 3D printing and have high temperature resistance to drying is a major challenge currently faced. Summary of the invention

[0006] The present invention aims to provide a photocurable 3D printing anti-drying conductive gel material and a preparation method and application thereof, which solves the problem that the existing photocurable 3D printing gel is easy to dry at high temperature and has poor elasticity, and takes into account good conductivity and mechanical properties.

[0007] The gel material provided by the present invention has good anti-drying property, and the gel will not lose solvent or deform its structure when placed indoors for a long time. The present invention constructs an anti-drying, photocurable 3D printable gel by introducing polyethylene glycol and strong coordination bonds into a covalent polymer network and utilizing the synergistic effect of non-covalent bonds and covalent bonds. The gel uses unsaturated polymers such as acrylic acid (AA) as monomers, polyethylene glycol (PEG) as solvent, zirconium ions are added to provide strong coordination for the gel, and zinc ions are added as conductive ions to give the gel conductivity. Under 405nm ultraviolet light irradiation, an organic gel network structure with strong coordination bonds is formed by free radical polymerization. This gel network exhibits excellent anti-drying property, high elasticity and printability.

[0008] The present invention provides a photocurable 3D printing anti-drying conductive gel material, which is prepared from the following components in parts by mass: Unsaturated polymer monomer: 40~60 parts Solvent: 40~60 parts Zirconium salt: 0.25~1 part Zinc salt: 0~14 parts Photoinitiator: 0.5~2 parts Light absorber: 0~0.03 parts The light absorber is adjusted according to the 3D printing machine. A general LCD printer does not need to add a light absorber, but a DLP printer does.

[0009] One of the unsaturated polymer monomers is acrylic acid, and the other monomer is one of N-isopropylacrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate, and N-vinylpyrrolidone; the mass ratio of the unsaturated polymer monomer acrylic acid to the other monomer is 1:4~4:1.

[0010] The solvent is polyethylene glycol, and the molecular weight of the polyethylene glycol is 200-600; the mass ratio of the two unsaturated polymer monomers to the polyethylene glycol is 4:6-6:4.

[0011] The zirconium salt is one of zirconium oxychloride and zirconium acetylacetonate; the zinc salt is one of zinc trifluoromethanesulfonate and zinc bis(trifluoromethanesulfonyl)imide.

[0012] The photoinitiator is one of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4.6-trimethylbenzoyl)phosphine oxide. The light absorber is one of lemon yellow, Sudan red I and Sudan red IV.

[0013] The present invention provides a method for preparing the above-mentioned light-cured 3D printing anti-drying conductive gel material, comprising the following steps: (1) First, two unsaturated polymer monomers are mixed, and then zirconium salt is added to the mixed unsaturated polymer monomers, and heated and stirred until uniformly dispersed to obtain a salt-containing monomer solution; the mass ratio of the zirconium salt to the unsaturated polymer monomer is 0.25-1:40-60; (2) dissolving the zinc salt in polyethylene glycol, heating and stirring until transparent and clear, to obtain a salt-containing polyethylene glycol solution; the mass ratio of the zinc salt to the polyethylene glycol is 0-14:40-60; (3) mixing the solutions obtained in step (1) and step (2) in a mass ratio of 40.25-61:40-74, and stirring the mixture at room temperature to obtain a gel solution; (4) Adding photoinitiators to the gel solution prepared in step (3) in sequence, stirring at room temperature until it is uniform and free of precipitation, thereby obtaining 3D printing gel ink; if a DLP printer is used, a light absorber needs to be added to the gel solution; (5) Slicing the STL format three-dimensional model using slicing software, pouring the gel ink prepared in step (4) into the material tank of the light-curing 3D printer for printing; (6) The gel printed in step (5) is ultrasonically cleaned with ethanol and then placed in a curing box for a second curing to obtain a light-cured 3D printed anti-drying conductive gel.

[0014] In the above preparation method, the heating temperature in step (1) and step (2) is 40 to 70°C.

[0015] The stirring speed in steps (1) to (4) is 600 to 1200 r / min.

[0016] The slice layer thickness described in step (5) is 0.03 to 0.1 mm, and the single layer curing time is 3 to 6 seconds.

[0017] The ultrasonic cleaning time in step (6) is 5 to 10 minutes, and the secondary curing time is 10 to 30 minutes.

[0018] The present invention provides an application of the above-mentioned light-cured 3D printing anti-drying gel in the preparation of soft materials, wherein the soft materials include flexible conductive materials, soft tissue preoperative models, hand-made models, etc.

[0019] Beneficial effects of the present invention: (1) The photocurable 3D printing anti-drying conductive gel provided by the present invention uses liquid polyethylene glycol with high vapor pressure instead of water as a solvent, has excellent anti-drying effect, and can be stably applied in the fields of flexible sensing, biomedicine, soft robots, and hand-made models.

[0020] (2) The anti-drying conductive gel provided by the present invention has good compatibility with the light-curing 3D printers on the market and can be used in various DLP and LCD printers and customized according to needs.

[0021] (3) The photocurable 3D printing anti-drying conductive gel provided by the present invention has adjustable adhesion, conductivity and mechanical properties, so that it can be used in a variety of scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The residual mass of the dumbbell-shaped gel prepared in Example 1 of the present invention after being exposed at room temperature for different periods of time.

[0023] Figure 2 This is a mechanical diagram of the dumbbell-shaped gel prepared in Example 2 of the present invention after 100 cycles.

[0024] Figure 3 It is a line graph of the residual strain and maximum stress of the dumbbell-shaped gel prepared in Example 2 of the present invention at the 1st, 20th, 40th, 60th, 80th and 100th cycles in 100 cycles.

[0025] Figure 4 This is the stress-strain diagram of the gel with different contents of zirconium salt in Example 3 of the present invention.

[0026] Figure 5 This is a graph showing the adhesion strength of the gel with different contents of zirconium salt to the copper sheet in Example 3 of the present invention.

[0027] Figure 6 This is a hollow pipe structure sample printed in Example 4 of the present invention.

[0028] Figure 7 This is a hollow structure sample printed by Example 4 of the present invention.

[0029] Figure 8 The finger sleeve model printed in Example 6 of the present invention and the wearing diagram.

[0030] Fig. 9 The electrical impedance diagrams obtained by bending the finger cuff printed in Example 6 of the present invention at different angles. DETAILED DESCRIPTION

[0031] The present invention is further illustrated by the following examples, but is not limited to the following examples. Example 1

[0032] Take three beakers and record them as beaker 1, beaker 2 and beaker 3 respectively. Add 24 parts of hydroxyethyl acrylate and 16 parts of acrylic acid to each of the three beakers, and then add 0.5 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide to each of them. After stirring and dissolving, continue to add 60 parts of deionized water to beaker 1, stir for 5 minutes to obtain a hydrogel precursor solution; add 60 parts of ethylene glycol (EG) to beaker 2, stir for 5 minutes to obtain an ethylene glycol gel precursor solution; add 60 parts of polyethylene glycol (PEG) 600 to beaker 3, stir for 5 minutes to obtain a polyethylene glycol gel precursor solution. Use a pipette to draw the above three gel precursor solutions into a dumbbell-shaped mold, irradiate for 100 seconds under light with a wavelength of 405nm, and obtain water-based gel, EG-based gel and PEG-based gel samples.

[0033] In this example, three kinds of gels were prepared according to three different solvents to evaluate the anti-drying performance of the gels. The three kinds of gels were exposed and placed in a 50°C drying oven to compare their anti-drying performance. The results are as follows: Figure 1 As shown in the figure, after being placed in a dry environment at 50°C for 72 hours, the mass loss of PEG-based gel was less than 1%, which was much lower than that of water-based gel and EG-based gel. The three gels were exposed to the air at room temperature for two months, and the weight of PEG-based gel increased by 1.46%, indicating that PEG-based gel has excellent anti-drying properties.

[0034] In this example, three kinds of gels were compared, and it was found that the anti-drying performance of polyethylene glycol-based gel was better than that of water-based gel and EG-based gel. Example 2

[0035] Add 30 parts of hydroxyethyl acrylate and 20 parts of acrylic acid to a beaker, then add 1 part of ZrOCl2·8H2O, add a magnet and place in a water bath, stir at 70°C for 10 min. Then add 50 parts of polyethylene glycol 400 and 5 parts of zinc trifluoromethanesulfonate, continue stirring at 50°C until the solution is clear. Finally, add 0.7 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, stir at room temperature in the dark until fully dissolved, and obtain PHAZ gel solution. Take the solution and put it into a dumbbell-shaped silicone mold, irradiate it with light of a wavelength of 405nm for 100s, and obtain a dumbbell-shaped tensile part for mechanical testing.

[0036] This example tests the elasticity and tensile stability of the gel material: a dumbbell-shaped specimen is subjected to 100 50% tensile cycle tests ( Figure 2 ), showing that in 100 cycles, the residual strain of the gel was less than 8%, and the maximum stress was maintained at 90 kPa ( Figure 3 ), indicating that the gel has good elasticity and good tensile stability. Example 3

[0037] Take four beakers, record them as beaker 1, beaker 2, beaker 3 and beaker 4, add 30 parts of hydroxyethyl acrylate and 20 parts of acrylic acid to the four beakers, add 0.25, 0.5, 0.75 and 1 parts of ZrOCl2·8H2O to them, stir them in a water bath at 60℃ until they are evenly dispersed, then move them to a magnetic stirrer and stir them at room temperature to cool to room temperature, then add 50 parts of polyethylene glycol 600, 5 parts of zinc trifluoromethanesulfonate and 0.7 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide to them, stir and dissolve them at 60℃ in the dark, and obtain polyethylene glycol gel precursor solution. Use a pipette to draw the above four gel precursor solutions into dumbbell-shaped molds, irradiate them under light with a wavelength of 405nm for 100s, and obtain four dumbbell-shaped tensile parts with different zirconium salt contents.

[0038] This example tests the mechanical properties and the adjustability of the adhesion of the gel material: stress-strain tests are performed on dumbbell-shaped tensile pieces with four different zirconium salts ( Figure 4 ) and adhesion test ( Figure 5 ), it was found that with the increase of zirconium salt content, the number of coordination bonds increased, the fracture strength of the gel increased significantly, and because the coordination bonds occupied a part of the hydroxyl groups, the adhesion of the gel decreased significantly. This reflects the adjustability of the tensile strength and adhesion strength of this gel material, so that the performance of the gel can be adjusted according to needs. Example 4

[0039] Add 36 parts of hydroxyethyl acrylate and 24 parts of acrylic acid to a beaker, then add 1 part of ZrOCl2·8H2O, add a magnet and place in a water bath, stir at 70°C for 10 min. Then add 40 parts of polyethylene glycol 400 and 10 parts of zinc trifluoromethanesulfonate, continue stirring at 50°C until the solution is clear. Finally, add 0.7 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and 0.03 parts of lemon yellow, stir at room temperature away from light until fully dissolved, and obtain PHAZ gel solution, which is printing ink, and store it for use; Printing of PHAZ gel: Pour the prepared printing ink into the liquid tank of the DLP 3D printer and print according to the following printing parameters as required.

[0040]

[0041] This embodiment uses a DLP 3D printer to print complex structures with high precision. After printing, the model is taken out, ultrasonically cleaned in alcohol for 2 minutes, and then placed in a curing box for curing for 10 minutes to obtain the final required model sample.

[0042] This embodiment prints high-precision hollow tubular channels and hollow structure models. Figure 6 It is a 1*1.5mm rectangular pipe. Ink is added to the printed pipe, and the outline of the pipe is clearly visible. Figure 7 The printed hollow structure has structural details that are exactly the same as the original digital model. Example 5

[0043] Add 30 parts of hydroxyethyl acrylate and 20 parts of acrylic acid to a beaker, then add 0.5 parts of ZrOCl2·8H2O, add a magnet and place in a water bath, stir at 70°C for 10 min. Then add 50 parts of polyethylene glycol 400 and 14 parts of zinc trifluoromethanesulfonate, continue stirring at 50°C until the solution is clear. Finally, add 0.7 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, stir at room temperature away from light until fully dissolved, and obtain PHAZ gel solution, which is printing ink, and store it for use; Printing of PHAZ gel: Pour the prepared printing ink into the liquid tank of the LCD 3D printer and print according to the following printing parameters as required.

[0044]

[0045] This embodiment uses an LCD 3D printer to print complex structures with high precision. After printing, the model is taken out, ultrasonically cleaned in alcohol for 2 minutes, and then placed in a curing box for 10 minutes to obtain the final required model sample. The light intensity of the LCD 3D printing light source is weaker than that of the DLP 3D printing light source, so there is no need to add light absorbers, and the illumination time of each layer is also relatively increased. Example 6

[0046] Add 30 parts of hydroxyethyl acrylate and 20 parts of acrylic acid to a beaker, then add 0.5 parts of ZrOCl2·8H2O, add a magnet and place in a water bath, stir at 70°C for 10 min. Then add 50 parts of polyethylene glycol 400 and 14 parts of zinc trifluoromethanesulfonate, continue stirring at 50°C until the solution is clear. Finally, add 0.7 parts of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and 0.01 parts of lemon yellow, stir at room temperature away from light until fully dissolved, and obtain PHAZ gel solution, which is printing ink, and store it for use; Printing of PHAZ gel: Pour the prepared printing ink into the liquid tank of the DLP 3D printer, set the printing parameters of the 3D printer according to the requirements, and print. After printing, take out the model, put it in alcohol for ultrasonic cleaning for 2 minutes, and then put it in the curing box for curing for 10 minutes to obtain the final required model sample.

[0047] In this embodiment, a customized finger cuff model was printed, and an electrical stability test was performed by wearing the finger cuff. Figure 8 The printed finger sleeves can fit your fingers perfectly. Fig. 9 It is an electrical sensing test performed on the finger wearing the finger cuff. The bending angle of the finger can be distinguished by the detected signal curve, indicating that the gel has good conductivity and electrical stability.

Claims

1. A light-cured 3D printing anti-drying conductive gel material, characterized in that: It is prepared from the following components in parts by weight: Unsaturated polymer monomer: 40~60 parts; Solvent: 40~60 parts; Zirconium salt: 0.25~1 part; Zinc salt: 0-14 parts; Photoinitiator: 0.5~2 parts; Light absorber: 0~0.03 parts.

2. The light-cured 3D printing anti-drying conductive gel material according to claim 1, characterized in that: The unsaturated polymer monomers include two types, one of which is acrylic acid, and the other monomer is one of N-isopropylacrylamide, hydroxyethyl acrylate, hydroxyethyl methacrylate, and N-vinylpyrrolidone; the mass ratio of the provided unsaturated polymer monomer acrylic acid to the other monomer is 1:4~4:

1.

3. The light-cured 3D printing anti-drying conductive gel material according to claim 1, characterized in that: The solvent is polyethylene glycol, and the molecular weight of the polyethylene glycol is 200-600; the mass ratio of the two unsaturated polymer monomers to the polyethylene glycol is 4:6-6:

4.

4. The light-cured 3D printing anti-drying conductive gel material according to claim 1, characterized in that: The zirconium salt is one of zirconium oxychloride and zirconium acetylacetonate; the zinc salt is one of zinc trifluoromethanesulfonate and zinc bis(trifluoromethanesulfonyl)imide.

5. The light-cured 3D printing anti-drying conductive gel material according to claim 1, characterized in that: The photoinitiator is one of diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; the light absorber is one of lemon yellow, Sudan red I and Sudan red IV.

6. A method for preparing a light-cured 3D printing anti-drying conductive gel material according to any one of claims 1 to 5, characterized in that The following steps are involved: (1) First, two unsaturated polymer monomers are mixed, and then zirconium salt is added to the mixed unsaturated polymer monomers, and heated and stirred until uniformly dispersed to obtain a salt-containing monomer solution; the mass ratio of the zirconium salt to the unsaturated polymer monomer is 0.25-1:40-60; (2) dissolving the zinc salt in polyethylene glycol, heating and stirring until transparent and clear, to obtain a salt-containing polyethylene glycol solution; the mass ratio of the zinc salt to the polyethylene glycol is 0-14:40-60; (3) mixing the solutions obtained in step (1) and step (2) in a mass ratio of 40.25-61:40-74, and stirring the mixture at room temperature to obtain a gel solution; (4) adding photoinitiators to the gel solution obtained in step (3) in sequence, stirring at room temperature until the solution is uniform and free of precipitation, thereby obtaining 3D printing gel ink; (5) Slicing the STL format three-dimensional model using slicing software, pouring the gel ink prepared in step (4) into the material tank of the light-curing 3D printer for printing; (6) The gel printed in step (5) is ultrasonically cleaned with ethanol and then placed in a curing box for a second curing to obtain a light-cured 3D printed anti-drying conductive gel.

7. The method for preparing a light-cured 3D printing anti-drying conductive gel material according to claim 6, characterized in that: In step (4), if a DLP 3D printer is used, a light absorber needs to be added to the gel solution.

8. The method for preparing a light-cured 3D printing anti-drying conductive gel material according to claim 6, characterized in that: The heating temperature in step (1) and step (2) is 40 to 70° C.; the stirring speed in steps (1) to (4) is 600 to 1200 r / min.

9. The method for preparing a light-cured 3D printing anti-drying conductive gel material according to claim 6, characterized in that: The slice layer thickness described in step (5) is 0.03-0.1 mm, and the single layer curing time is 3-6 s; the ultrasonic cleaning time described in step (6) is 5-10 min, and the secondary curing time is 10-30 min.

10. Use of the photocurable 3D printing anti-drying conductive gel material according to any one of claims 1 to 5 in the preparation of soft materials, wherein the soft materials include flexible conductive materials, soft tissue preoperative models or hand-made models.

Citation Information

Patent Citations

  • Dynamic ion cross-linked polyacrylic acid-polyethylene glycol hydrogel binding agent and preparation method and application thereof

    CN109888286A

  • Self-healing conductive ionic gel as well as preparation method and application thereof

    CN111848982A

  • Conductive hydrogel as well as preparation method and application thereof

    CN114671963A

  • Application of high-strength hydrogel as printing ink in photocuring 3D printing

    CN114958079A

  • Pure physical network hydrogel as well as preparation method and application thereof

    CN117924745A